The Effectiveness of Using RealLife English Application to Improve Students’ Speaking Ability at Grade XI of SMK Negeri 4 Pekanbaru - Sari, Nadila Permata; Febtiningsih, Prih; Pahmi, Pahmi (FKIP - Universitas Riau, 2025)
This study investigates the effectiveness of RealLife English application in improving speaking skills in eleventh grade students at SMK Negeri 4 Pekanbaru. It was found that the problems were limited vocabulary, lack of confidence, and inadequate use of interactive media. This study used a quantitative approach using a quasi-experimental design where the experimental group used RealLife English application and the control group used conventional methods. The study consisted of 75 students randomly selected from two classes: Accounting 2 Class (experimental) and Batik and Textile Creative Craft 1 Class (control). Quantitative data was collected through pre-test and post-test, by analyzing the improvement of speaking ability. The experimental group showed a significant increase in their mean score from 55.55 to 75.55. In contrast, the average score of the control group increased from 41.53 to 58.05. Statistical analysis confirmed that the improvement in the experimental group was significant p-value = 0.000, thus it can be concluded that the alternative hypothesis analysis (Ha) is accepted. These findings indicate that the RealLife English application significantly improved students' speaking ability compared to the conventional method. This research highlights the potential of the application to offer a more engaging and interactive learning experience.